2015
DOI: 10.1111/1462-2920.13087
|View full text |Cite
|
Sign up to set email alerts
|

Carbon roadmap from syngas to polyhydroxyalkanoates in Rhodospirillum rubrum

Abstract: The gasification of organic waste materials to synthesis gas (syngas), followed by microbial fermentation, provides a significant resource for generating bioproducts such as polyhydroxyalkanoates (PHA). The anaerobic photosynthetic bacterium, Rhodospirillum rubrum, is an organism particularly attractive for the bioconversion of syngas into PHAs. In this study, a quantitative physiological analysis of R. rubrum was carried out by implementing GC-MS and HPLC techniques to unravel the metabolic pathway operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 53 publications
3
72
1
Order By: Relevance
“…This indicated that CO 2 present in syngas can be more readily converted into acetyl-CoA, which is then subjected to fatty acid synthesis, than can CO, which has to be oxidized by the CO dehydrogenase in R. rubrum to CO 2 at first (42). Recently, Revelles et al (16) showed an upregulation of genes coding for additional carboxylases, other than RubisCO, which play a major role in the fixation of CO 2 in R. rubrum when acetate is present in the cultivation medium but not with malate. Therefore, the use of another citric acid cycle intermediate, such as succinate, as an auxiliary carbon source should likewise not lead to an upregulation of the acetate assimilation route ethylmalonyl-CoA pathway or acetylCoA carboxylation via PFOR (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicated that CO 2 present in syngas can be more readily converted into acetyl-CoA, which is then subjected to fatty acid synthesis, than can CO, which has to be oxidized by the CO dehydrogenase in R. rubrum to CO 2 at first (42). Recently, Revelles et al (16) showed an upregulation of genes coding for additional carboxylases, other than RubisCO, which play a major role in the fixation of CO 2 in R. rubrum when acetate is present in the cultivation medium but not with malate. Therefore, the use of another citric acid cycle intermediate, such as succinate, as an auxiliary carbon source should likewise not lead to an upregulation of the acetate assimilation route ethylmalonyl-CoA pathway or acetylCoA carboxylation via PFOR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The purple nonsulfur alphaproteobacterium Rhodospirillum rubrum is able to utilize CO and CO 2 and has been a host and model organism for several studies focusing on the synthesis of PHA SCL from various feedstocks (14)(15)(16). Applying the water-gas shift reaction, R. rubrum oxidizes CO with H 2 O to CO 2 and H 2 , employing a carbon monoxide dehydrogenase (CODH), thereby gaining energy and carbon that is channeled into the Calvin cycle via ribulose 1,5 bisphosphate carboxylase (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By selecting the appropriate microorganism, a wide range of valuable products can be synthesized, such as PHAs, isoprene, lactic acid and methane (www.celbicon.org). For example, Rhodospirillum rubrum, a purple non-sulfur bacterium, can produce PHAs from CO as carbon and energy source (Revelles et al, 2016). This feature and its metabolical versatility make this species interesting as biological tool for CO 2 fixation.…”
Section: Indirect Eetmentioning
confidence: 99%